THE SCIENTIFIC BACKGROUND OF METHODS FOR INCREASING SUSTAINABILITY UNDERGROUND MINING WITH THE USE OF ANCHORING (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
An analysis of a large number of literary sources on the practice of constructing underground structures shows that it is the type of support, technology, and mechanization of its construction that predetermine the speed of mining and greatly influence the quality of tunneling work.